2017
DOI: 10.24171/j.phrp.2017.8.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Body-related Perspectives and Weight Control Methods of Korean-Chinese Nursing School Students in Yanbian, China: A Pilot Study

Abstract: ObjectivesThis study aimed at identifying the current nutrition knowledge, body-related perspectives, and weight control behaviors of Korean-Chinese college students.MethodsWe conducted a pilot study by employing a healthy weight education program targeting Korean-Chinese nursing school students at the Yanbian University of Science and Technology in Yanbian, China.ResultsThis pilot study included 40 participants (38 women and 2 men; mean age, 20.5 years). The current weight status of the participants was as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…To compare the level of physical inactivity, the Shapiro-Wilks normality test was initially performed, followed by Kruskal-Wallis with Dunn's post hoc test with a 5% significance level. Like our study, other authors also found higher physical inactivity among females [29][30][31] with a consequent increase in the rates of obesity [12][13][14] , diabetes mellitus, hypercholesterolemia, metabolic syndrome, and hypertension 32 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To compare the level of physical inactivity, the Shapiro-Wilks normality test was initially performed, followed by Kruskal-Wallis with Dunn's post hoc test with a 5% significance level. Like our study, other authors also found higher physical inactivity among females [29][30][31] with a consequent increase in the rates of obesity [12][13][14] , diabetes mellitus, hypercholesterolemia, metabolic syndrome, and hypertension 32 .…”
Section: Discussionsupporting
confidence: 86%
“…From 2006 to 2017, the frequency of overweight adults increased by an average of 1.14%/year and obese adults by 0.67%/year; following this trend, the frequency of individuals diagnosed with diabetes increased by an average 0.24%/year 10 . The problems resulting from global physical inactivity are related to metabolic syndrome 11 , overweight 12,13 , and dementia 14, among others 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, social interest in weight control has recently increased, and weight control products and programs are widespread. However, according to studies involving Korean women, the most frequently used weight control methods were diet-related and included fasting, meal size reduction, and skipping meals [ 8 , 13 ]; and 30.7% of women engaged in weight-control programs experienced adverse effects [ 14 ]. The finding that weight-control behavior can increase, rather than decrease, harmful effects on health suggests a need for an in-depth understanding of weight-control behavior from a health-promotion perspective.…”
Section: Introductionmentioning
confidence: 99%